Dampak Persepsi Harga dan Citra Merek pada Attitudinal Loyalty Konsumen Skincare Innisfree - Halim, Michelle (Jurnal Manajemen, 2023)
Price perception and brand image are prominent factors that influence consumers' propensity to buy a product. However, in the context of high credence product, their influence on brand loyalty is still in open to study. Using Innisfree as a research context, the researcher aims to study whether the two variables affect attitudinal loyalty. For that purpose, the researchers constructively replicated Adawiah's (2015) research model by adding attitudinal loyalty as an endogenous variable and price perception and brand image as exogenous variables. Data were collected using Google Forms from 150 respondents selected purposively. The analysis using Structural Equation Modeling with WarpPLS 7.0 shows that price perception and brand image have a positive and significant effect on the attitudinal loyalty. Further research can involve behavioral loyalty as an additional endogenous variable.